2016
DOI: 10.1016/j.ijplas.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Deformation and strain localization in polycrystals with plastically heterogeneous grains

Abstract: A model of a polycrystalline material is studied, where each grain consists of several zones with different plastic properties. The size and configuration of the zones as well as their properties are mimicking the situation inside the crystals of artificially aged Al alloys with precipitate free zones (PFZs). The properties of the different zones are conjectured based on micromechanical models and experimental observations of the AA6000 series of Al alloys. A periodic patch of such a composite material, subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 74 publications
1
13
0
Order By: Relevance
“…The AA6060 aluminium alloy used in this study has been investigated in several other studies, and the reader is referred to these previous works for details, while a short summary is presented here 3234 . The alloy contained 0.422 wt% Si and 0.468 wt% Mg, and was extruded as a 10 mm thick profile measuring 83 mm in width.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The AA6060 aluminium alloy used in this study has been investigated in several other studies, and the reader is referred to these previous works for details, while a short summary is presented here 3234 . The alloy contained 0.422 wt% Si and 0.468 wt% Mg, and was extruded as a 10 mm thick profile measuring 83 mm in width.…”
Section: Methodsmentioning
confidence: 99%
“…All of the observed precipitates were consistent with the β″ phase, except for relatively few inhomogeneously nucleated precipitates that were of an over-aged character. The material has an equiaxed grain structure with a strong cube texture and minor Goss components 32,33 .…”
Section: Methodsmentioning
confidence: 99%
“…In addition to Schwellinger [4] there are several studies that have reported on dislocation structures in PFZs of aluminium alloys [15][16][17][18]. Styczyńska et al [15] observed by in situ TEM straining experiments that dislocation sources at GBs became active before sources inside the grain interiors.…”
Section: Introductionmentioning
confidence: 99%
“…Watanabe et al [17] did not study PFZs specifically, but noted that some PFZs in an Al-Mg-Sc alloy under cyclic loading became misoriented relative to their parent grains. Khadyko et al [18] observed several different dislocation structures in PFZs and their vicinity in an Al-Mg-Si alloy stretched to fracture in uniaxial tension. In most PFZs, both inside and outside the neck, dislocations spanned the PFZs and appeared almost perpendicular to the GB plane.…”
Section: Introductionmentioning
confidence: 99%
“…These activities contribute to the understanding of the failure mechanisms (e.g. Baczmanski et al 2016, Kim and Yoon (2015), Matsuno et al (2015), De Geus et al 2016, Daehli et al (2016), Khan and Bhasin (2017), Khadyko et al (2016), Lee et al (2015), Scales et al, 2016) and the development of enhanced porous plasticity models to predict ductile failure (Tutyshkin et al (2015), Zhai et al (2016), Shutov et al (2015), Ling et al (2016)). In real materials, the effect of anisotropy on ductile failure is also often relevant.…”
Section: Introductionmentioning
confidence: 99%